ANALISIS YURIDIS AKIBAT HUKUM TIMBULNYA PEMUTUSAN KONTRAK SECARA SEPIHAK TERHADAP INVESTOR PADA PERJANJIAN BOT (BUILD OPERATE TRANSFER) - Imelda Fertikel Putri Handayani (CV. KAMPUS AKADEMIK PUBLISING, 2023)
. The contract in a Build-to-Transfer agreement that is starting to develop is known as a BOT Agreement or Build Operate Transfer, referring to a project transfer method that is often used in large infrastructure projects. Is a private legal entity that obtains a business license from the government or public sector to finance, design and build, implement and own a project within a certain period of time. The aim is for the private sector to get back the results of its investment and then transfer project management to the government or public sector. However, if in the process there is a unilateral termination of the contract, the party being terminated will have legal consequences that will cause loss or suffering for him. So my writing analyzes the legal consequences that arise from conflicts or implications in cases of unilateral contract termination by the government or the public sector so that investors' rights are maintained and are not harmed.